A national system for monitoring the population of agricultural pests using an integrated approach of remote sensing data from in situ automated traps and satellite images - Themistocleous, Kyriacos; Psimolophitis, Elias; Hadjimitsis, Diofantos G. (My University, 2010)
A national system for monitoring the population increase of agricultural pest "Lobesia Botrana" (vine moth/fly that attacks grapes) in Cyprus has been developed. The system comprises of automated delta traps with GPS that use wireless(Wi-Fi) camera, automated image analysis for identification of the specific fly species, Wi-Fi technology for transferring the data using mobile telephony network to a central station for result presentation and analysis. A GIS database was developed and included details of the pilot vineyards, environmental conditions and daily data of the number of captured flies from each automated trap. The results were compared with MODIS and LANDSAT satellite thermal images since the appearance of the vine fly is greatly dependent on the microclimate temperatures (degree days). Results showed that satellite data can estimate accurately the appearance of the vine fly. The proposed system can be an important tool for the improvement of a national Integrated Pest Management (IPM) system and it can also be used for monitoring other agricultural pests and insects
Keywords: Agricultural; MODIS; Pest; Temperature; Thermal satellite images; Trap; Vine-fly